2007
DOI: 10.1111/j.1574-6968.2006.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli dinJ-yafQgenes act as a toxin-antitoxin module

Abstract: Bacterial toxin-antitoxin (TA) systems are operons that code for a stable toxic protein and a labile antitoxin. TA modules are widespread on the chromosomes of free-living Bacteria and Archaea, where they presumably act as stress response elements. The chromosome of Escherichia coli K-12 encodes four known TA pairs, as well as the dinJ-yafQ operon, which is hypothesized to be a TA module based on operon organization similar to known TA genes. Induction of YafQ inhibited cell growth, but its toxicity was counte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
63
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 22 publications
4
63
0
Order By: Relevance
“…In contrast, the antitoxins in the RelE-RelB (n ϭ 2), aRelE-aRelB (n ϭ 2), YoeBYefM (n ϭ 1), and MazF-MazE (n ϭ 4) complexes form dimers (toxin n -antitoxin 2 (7,12,21,38)). It has been suggested that the YafQ-DinJ complex comprises two toxin and two antitoxin molecules (39). Dimerization of antitoxins can be related to observations showing that the antitoxins regulate the TA operon by interacting with DNA as homodimers (7,38,40,41).…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, the antitoxins in the RelE-RelB (n ϭ 2), aRelE-aRelB (n ϭ 2), YoeBYefM (n ϭ 1), and MazF-MazE (n ϭ 4) complexes form dimers (toxin n -antitoxin 2 (7,12,21,38)). It has been suggested that the YafQ-DinJ complex comprises two toxin and two antitoxin molecules (39). Dimerization of antitoxins can be related to observations showing that the antitoxins regulate the TA operon by interacting with DNA as homodimers (7,38,40,41).…”
Section: Discussionmentioning
confidence: 98%
“…(His) 6 DinJ-YafQ protein complex was obtained after overexpression of pRSETdinJyafQ plasmid (Table 1) in BL21 strain, and (His) 6 DinJ protein was purified from (His) 6 DinJ-YafQ protein complex as described earlier (33). RNA cleavage analysis in vitro.…”
Section: Methodsmentioning
confidence: 99%
“…We have shown earlier that E. coli YafQ toxin exhibits high structural similarity to RelE family of toxin RNases such as E. coli YoeB and Pyrococcus horikoshii RelE (33). More recently, Prysak et al (42) demonstrated that YafQ specifically cleaves E. coli mRNA's exclusively at AAA (Lys) codons in the ribosome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6,7) The Escherichia coli chromosome encodes at least five TA systems, RelB-RelE, MazE-MazF, ChpBIChpBK, YefM-YoeB, and DinJ-YafQ. 8) Toxins MazF, ChpBK, YoeB, and YafQ have been found to have intrinsic RNase activity in vitro; they are hence referred to as mRNA interferases. 9) However, a recent study found that mRNA cleavage by YoeB and YafQ was strictly dependent on translation of the mRNA in vivo, whereas site-specific mRNA cleavage by MazF occurred independently of translation in vivo.…”
mentioning
confidence: 99%